Sistema de administración web de usuarios, para los pagos y registros de usuarios de la empresa Cybernet sistemas comunicaciones y redes (2021)
This document describes the operation of the Web Administration System of the CYBERNET company, from the way to access the application to the use of each of the functionalities.